P168 Modulating cortical excitability of human motor cortex by β- and γ-band transcranial alternating current stimulation (tACS). Issue 3 (March 2017) - Nowak, M.; Hinson, E.; Guerra, A.; Pogosyan, A.; van Ede, F.; Quinn, A.; Brown, P.; Stagg, C.
Abstract : Introduction: Transcranial alternating current stimulation (tACS) is a non-invasive technique capable of interacting with endogenous brain oscillations in a frequency-specific manner (Zaehle et al., 2010; Feurra et al., 2011). Synchronized oscillatory activity at beta (15–30 Hz) and gamma (30–90 Hz) frequency range is of particular importance in the motor system. Importantly, recent work on tACS has provided evidence that beta and gamma oscillations are causally linked to aspects of motor behavior (Pogosyan et al., 2009; Joundi et al., 2012). Despite this, little is known about the mechanisms underlying tACS. The present study investigated the effects of beta- and gamma-frequency tACS on various measures of cortical excitability, as indexed by TMS. Methods: Subjects participated in five experimental sessions separated by at least one week. In Session 1, all subjects had a MEG scan in order to determine individual beta and gamma peak frequency for subsequent tACS sessions. In Sessions 2–4, subjects underwent tACS at beta, low gamma, high gamma frequency or a sham stimulation. tACS was applied for 20 min over the left M1 and the contralateral orbit at intensity adjusted below individual phosphene- and discomfort threshold. TMS protocols, including a single-pulse MEP, SICI2.5 ms and ICF, were performed at rest before, during (at 5 and 15 min) and after tACS. A single MEP and SICI2.5 ms were also recorded during movement preparation before and after tACS. Results: High gamma tACS increased single-pulse MEP and decreased SICI amplitudes during 15 min and 5 min of tACS, respectively, when compared to sham. Conversely, the opposite trend was observed for a single-pulse MEP at 5 min and SICI at 15 min. In both cases, within-session changes from baseline at an early time point were correlated with those at a later time point during stimulation. No inter-protocol correlations were found at 5 min or 15 min during high gamma tACS. No after-effects of tACS were observed in any of the stimulation sessions as compared to sham. Conclusions: Single-pulse MEP and SICI amplitudes reflecting general corticospinal excitability and GABAA -mediated inhibition at the level of the primary motor cortex, respectively, were affected online in a duration-dependent manner by high gamma tACS. These changes resemble homeostatic-like plasticity, although no effect lasting beyond the stimulation period was observed. In addition, changes observed early could predict subsequent changes later on during stimulation.